2011
DOI: 10.1016/j.virol.2011.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Structure–function analysis of receptor-binding in adeno-associated virus serotype 6 (AAV-6)

Abstract: Crystal structures of the AAV-6 capsid at 3 Å reveal a subunit fold homologous to other parvoviruses with greatest differences in two external loops. The electrostatic potential suggests that receptor-attachment is mediated by four residues: Arg576, Lys493, Lys459 and Lys531, defining a positively charged region curving up from the valley between adjacent spikes. It overlaps only partially with the receptor-binding site of AAV-2, and the residues endowing the electrostatic character are not homologous. Mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
69
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 57 publications
(87 reference statements)
1
69
0
Order By: Relevance
“…The 3-fold symmetry axes on AAV capsids have been associated with glycan receptor recognition in the cases of AAV2, AAV3b, AAV6, and AAV9 (25)(26)(27)(28)(29)(30)(31). The surface protrusions and spikes surrounding the 3-fold axes are predominantly composed of the highly dynamic GH loop connecting the ␤G and ␤H strands within the capsid protein subunit (10,11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3-fold symmetry axes on AAV capsids have been associated with glycan receptor recognition in the cases of AAV2, AAV3b, AAV6, and AAV9 (25)(26)(27)(28)(29)(30)(31). The surface protrusions and spikes surrounding the 3-fold axes are predominantly composed of the highly dynamic GH loop connecting the ␤G and ␤H strands within the capsid protein subunit (10,11).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, key basic residues (R484, R487, K532, R585, and R588) involved in heparan sulfate recognition have now been located on 3-fold protrusions of the AAV2 capsid (25,27,29,41). Similarly, heparan sulfate recognition by AAV3B and AAV6 capsids is now well established (26,28,31). In the case of AAV9, the residues D271, N272, N470, Y446, and W503 are required for Gal binding (30).…”
Section: Discussionmentioning
confidence: 99%
“…These studies were initiated to identify VRs on the surface of AAV9 that might be responsible for its enhanced tissue transduction compared to those of other AAV serotypes. The AAV9 cryoreconstruction revealed and the higher-resolution X-ray crystal structure confirmed that VR-I and VR-IV adopt surface loop conformations in AAV9 that are unique compared to those of AAV2, AAV3b, AAV4, AAV6, and AAV8, for which high-resolution crystal structures are available (27,41,51,53,78,79). Significantly, VR-I and VR-IV amino acids as well as other VR regions have been reported to control the transduction phenotype in AAV1, AAV2, AAV6, and AAV8 (44) as well as AAV9 (37,43,60).…”
mentioning
confidence: 77%
“…The entire sequence of VP3 is contained within VP2, and all of VP2 is contained within VP1, which has a unique N-terminal (VP1u) domain. Only the common VP3 region is observed in all of the capsid structures of AAV serotypes determined to date, either by cryo-electron microscopy (cryo-EM) and image reconstruction (cryo-reconstruction) or by X-ray crystallography (27,39,41,50,51,53,56,72,78,79). Comparisons of the AAV structures show that the core of each VP contains an eight-stranded ␤-barrel motif (␤B to ␤I) and an ␣-helix (␣A) that are also conserved in autonomous parvovirus capsids.…”
mentioning
confidence: 99%
See 1 more Smart Citation